2004
DOI: 10.1089/hum.2004.15.878
|View full text |Cite
|
Sign up to set email alerts
|

Protective Immunity Against Trypanosoma cruzi Infection in a Highly Susceptible Mouse Strain After Vaccination with Genes Encoding the Amastigote Surface Protein-2 and Trans-Sialidase

Abstract: Protective immunity against lethal infection is developed when BALB/c or C57BL/6 mice are immunized with plasmids containing genes from the protozoan parasite Trypanosoma cruzi. However, genetic vaccination of the highly susceptible mouse strain A/Sn promoted limited survival after challenge. This observation questioned whether this type of vaccination would be appropriate for highly susceptible individuals. Here, we compared the protective efficacy and the immune response after individual or combined genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
72
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(86 citation statements)
references
References 22 publications
12
72
0
2
Order By: Relevance
“…Such a strong immune response did not cause any discernible immunopathology. It in fact led to a reduced parasite development and prevented the establishment of chronic phase tissue pathologies (46,47). Also, some of these vaccinated mice completely cleared the parasite and established sterile immunity (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Such a strong immune response did not cause any discernible immunopathology. It in fact led to a reduced parasite development and prevented the establishment of chronic phase tissue pathologies (46,47). Also, some of these vaccinated mice completely cleared the parasite and established sterile immunity (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Upon plasmid immunisation, depletion of either CD4 + or CD8 + T cells completely reversed protective immunity, thus demonstrating a non-overlapping role for these two subpopulations (Katae et al 2002, Vasconcelos et al 2004. Following vaccination with recombinant protein of ASP-2 in alum and CpG ODN, only depletion of CD8 + , but not CD4 + , T cells reversed protective immunity (Araújo et al 2005).…”
Section: As Shown Inmentioning
confidence: 94%
“…To determine the role of immunisation in reducing chronic phase disease symptoms, a number of experiments using different animal models must be performed. In many of the models described above, tissue inflammation and parasitism in the late chronic phase were significantly reduced following prophylactic vaccination (Garg & Tarleton 2002, Vasconcelos et al 2004, Araújo et al 2005. Therefore it is possible that prophylactic vaccinations indeed halt the development of the chronic phase immunopathologies.…”
Section: As Shown Inmentioning
confidence: 99%
“…Under these circumstances, we obtained reduced parasitism and limited disease development. Also, in some cases, we reached sterile protection against T. cruzi, showing that vaccination could be a useful approach to boost the host immunodominant response (9)(10)(11)(12). We concluded that aberrantly high immunodominant responses may, in some cases, clear the parasite from the host.…”
mentioning
confidence: 73%
“…Based on that assumption, the means to break the deadlock is through increasing and/or broadening the immune responses prior to and/or during infection (9)(10)(11). Whether immunotherapy should focus on dominant, subdominant, or cryptic epitopes or on all of them at the same time can be addressed experimentally in the near future and may provide the basis for rational interventions.…”
mentioning
confidence: 99%